As implicações do programa 'São Paulo faz escola' no trabalho docente de professores iniciantes: um estudo de caso - Barros, Ricardo Abdalla [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study tried to propitiate reflections about teaching work of the teachers in the teaching of Portuguese Language and Literature area who work in the context of São Paulo state school with the implementation of the curriculum alteration by use of books in teaching activities – the Program São Paulo faz escola. For this we conducted a qualitative research through a case study in a public school in a city of countryside of the state of São Paulo, with three teachers who work in High School, in this area of knowledge, who were inserted like users of the above-mentioned material. In this study the accompaniment of these teachers was conducted in the first semester of 2013 through observations of classes, interviews and documental analysis of the activities performed in these classes, as well as the Curriculum Proposal of the State of São Paulo. Before the done work we point that, for teachers, this curriculum change impacted the classes of these teachers, because the curriculum impose, in many cases, the form and conception of teaching and learning that they should take forward the use of the books. It is visible, in the analyzed data, the feeling that was take away the authorship and the autonomy of professional intervention of these teachers, getting a teaching job in a much more utilitarian perspective of a predetermined curriculum. Moreover, we observe the daily pressure that the teachers suffer for the students can show high scores in purely quantitative exams of the instruments used by State Department of Education, disregarding completely the process and their own challenges experienced during the school year

professores iniciantes da área do ensino de Língua Portuguesa e Literatura que atuam no contexto da escola pública estadual paulista com a implementação da mudança curricular via utilização dos cadernos nas atividades docentes – o Programa São Paulo faz escola. Para isso realizamos uma pesquisa qualitativa por meio de um estudo de caso numa escola estadual de uma cidade do interior do estado de São Paulo, com três professores que atuam no Ensino Médio, nessa área de conhecimento, que se viram na condição de usuários do referido material. Nesse estudo foi realizado o acompanhamento desses docentes no primeiro semestre de 2013 por meio de observações das aulas, entrevistas individuais e análise documental das atividades realizadas nessas aulas, assim como da Proposta Curricular do Estado de São Paulo. Diante do trabalho realizado apontamos que, para os docentes, essa mudança curricular acabou por impactar as aulas que desenvolvem, pois acabam por ditar, em muitas vezes, a forma e a concepção de ensino e de aprendizagem que devem adotar frente à utilização dos cadernos. É visível nos dados analisados o sentimento de que foi retirado desses professores a autoria e a autonomia de intervenção profissional, ficando o trabalho docente muito mais numa perspectiva utilitarista de um currículo predeterminado. Além disso, observamos a pressão diária que os docentes sofrem para que os alunos, nas avaliações meramente quantitativas dos instrumentos utilizados pela Secretaria da Educação do Estado, apresentem notas altas, desconsiderando por completo o processo e os próprios desafios vividos no decorrer do ano letivo
Keywords: São Paulo Faz Escola; Teachers, Training of; Professores - Formação; Lingua portuguesa - Estudo e ensino; Literatura - Estudo e ensino; Ensino; Ensino - Curriculos